Indices in differentiating iron deficiency anemia from thalassemia trait- a comparative study - Ahmad, Sufia; Zaidi, Noorin; Mehdi, Syed Riaz; Irfan, Sumaiya; Ahmad, Sharique (Asian Journal of Medical Sciences, 2021)
Background: Iron deficiency anemia (IDA) and beta thalassemia trait (BTT) are the two most common and important causes of microcytic hypochromic anemia in India. It is very difficult to differentiate between the two. Many different types of techniques have been proposed for the same. While some are invasive like bone marrow examination others are not available at all centers, like electrophoresis. Hence different indices come into play. Aims and Objective: This study was undertaken to compare the efficacy of Shine and Lal index and Mentzer index in differentiating between IDA and BTT. Materials and Methods: A total of 407 anemia cases were studied over a period of 18 months and their blood samples were subject to different hematological and biochemical assays to diagnose the type of anemia. Results: Based on these tests 92.1% cases were found to be of IDA whereas 3.7% cases were found to be of BTT. Then both the indices were applied in the above mentioned cases. Conclusion: While Shine and Lal index was found to have better sensitivity, Mentzer index was found to have better specificity.